Effects of mathematical modeling on students' achievement and attitude towards mathematics - Adrao, Eugenio S. (Animo Repository, 2001)
This study determines the effects of mathematical modeling on the mathematics achievement and attitudes towards mathematics of fourth year high school students.The study was conducted among two of the seven fourth year classes at Quezon Science High School. The two classes were assigned at random into the control and the experimental groups. Both experimental and control groups participated in writing research paper of their own chosen topic in the application of Conics. Both groups also participated in the defense of their research paper. Experimental group alone has undergone the treatment of mathematical modeling. The researcher taught the experimental class while equally qualified mathematics teacher taught the control class. Both classes were taught the same content for ten weeks. Both groups were given pre and post achievement tests and pre and post experimental attitude scales to determine the possible changes in their mathematics achievement and attitudes toward mathematics as a result of the experiment.On the basis of the findings, the following conclusions were drawn:1) The math modeling has no significant effect on the improvement of math achievement of the students in conics when: each group has 8 or 9 members, and when modeling is employed for a duration of only 10 weeks for the topic on conics.2) Mathematical modeling has no significant effect on the attitudes of students towards mathematics.